(untitled) (Research, Society and Development, 2022)
The objective of this study was to characterize the cases of animal abuse and violence against women, as well as to verify the existence of an association among these cases in the city of Pinhais, Paraná, Brazil. Reports of animal abuse and violence against women between January 2017 and January 2019, received by the city’s monitoring institutions, were analyzed. To characterize the cases, a statistical analysis was performed using Excel® and R software. In relation to the animals, neglect of moderate severity was the type of abuse that most occurred. The Downtown neighborhood had the highest prevalence in all types of neglect and feline species was the most affected. In the cases of violence against women, the main aggressor was the ex-partner, with an average age of 39.15 years old. The victims presented an average age of 38.44 years old, and with a higher frequency of incomplete fundamental schooling and being employed. The most common violence was psychological, the Alto Tarumã and Downtown neighborhoods presented the highest prevalence. Case prevalence of animal abuse and violence against women per neighborhood showed an inconclusive relation. Therefore, it is concluded that a joint evaluation of the cases involving animal abuse and interpersonal violence is indispensable, establishing communication among institutions for an effective confrontation network and reinforces the need for public policies that recognize the Link.